A classical mechanics problem by Miraj Shah

Consider a body, attached to a string of length r r , to be initially at rest in the vertical plane. It can be proved that if we give the body an initial velocity of v > 5 g r v>\sqrt{5gr} , then, the body can make complete revolutions in the vertical plane about the point of suspension.

Let us consider that the body, initially at rest, is given a velocity v < 5 g r v<\sqrt{5gr} . If at this value of v v the body eventually hits the point of suspension then we can write:

v 2 = ( a + b ) g r . v^2 = (a+\sqrt{b})gr \; .

Find a × b a\times b .


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Miraj Shah
Mar 26, 2016

After the instant, when tension in the string becomes zero, the body does not perform circular motion but instead follows a parabolic path. Let the velocity of the body at the instant tension in the string becomes zero, be u u as shown in the figure. Let the time taken from this instant to reach the point of suspension be t t .

Therefore,

t = 2 u g cos θ \large \boxed{t = \dfrac{2u}{g\cos\theta}} .... ( 1 ) (1)

Also, at the exact instant when the tension in the string becomes zero, we can write the equation of motion as follows:

Net Force towards Centre = m u 2 r \large \dfrac{mu^2}{r}

m g sin θ = m u 2 r \Rightarrow mg\sin\theta = \large \dfrac{mu^2}{r}

u 2 = g r sin θ \Rightarrow \boxed{u^2 = gr\sin\theta} .... ( 2 ) (2)

Now, we also know that the horizontal component of u u is u x = u sin θ u_x=u\sin\theta

Therefore,

( u x ) ( t ) (u_x)(t) = Net displacement in the horizontal direction.

( u sin θ ) ( t ) = r cos θ (u\sin\theta)(t) = r\cos\theta

2 u 2 sin θ = g r cos 2 θ \Rightarrow 2u^2\sin\theta = gr\cos^2\theta ....(from equation ( 1 ) (1) )

2 g r sin 2 θ = g r cos 2 θ \Rightarrow 2gr\sin^2\theta = gr\cos^2\theta ....(from equation ( 2 ) (2) )

tan θ = 1 2 sin θ = 1 3 u 2 = g r 3 \Rightarrow \tan\theta = \dfrac{1}{\sqrt{2}} \Rightarrow \sin\theta = \dfrac{1}{\sqrt{3}} \Rightarrow \boxed{\large u^2 = \dfrac{gr}{\sqrt{3}}}

Now that we know the value of u 2 u^2 we can use the Law of Conservation of Energy to find v 2 v^2

On calculating we get:

v 2 = g r ( 2 + 3 ) v^2 = gr(2+\sqrt 3)

Therefore, a b = 6 \boxed{ab = 6}

I'm not very good at kinematics - how do you arrive at equation 1? Thanks.

Shaun Leong - 5 years, 2 months ago

Log in to reply

Refer to the figure above.

We know that the formula for time of flight in general for a body performing projectile motion is t = 2 u y a y t=\large \frac{2u_y}{a_y} .

Here u y u_y = Magnitude of velocity of the body in the vertical direction and

a y a_y = Magnitude of acceleration of body in the vertical direction

As you can see from the figure above, here u y = u u_y=u and a y = g c o s θ a_y=gcos\theta . Plugging in the values we get t = 2 u g c o s θ t= \large \frac{2u}{gcos\theta} .

If you still have any doubt or problem regarding this or any other part of the solution feel free to ask.

And sorry for replying to your question a bit late!

Miraj Shah - 5 years, 2 months ago

Log in to reply

Oh.. thanks! I tried to make u into its velocity components rather than g and wondered how you arrived at a division by cos θ \cos \theta . This helped me a lot.

Shaun Leong - 5 years, 2 months ago
Rohith M.Athreya
Mar 27, 2016

let us consider the string to become slackened at an angular position \(\theta) measured from horizontal in anticlockwise direction.

at this point, tension in string is zero.

thus \(mgsin\theta=\frac{mv^{'2}}{r}\) where v v^{'} is the velocity at point of slackening.

thus v = g r s i n θ v^{'}=\sqrt{grsin\theta}

from this point onwards, the path of ball is parabolic with general equation being,

y = x c o t θ g x 2 2 v 2 s i n 2 θ y = xcot\theta- \frac{gx^{2}}{2v^{'2} sin^{2} \theta}

plugging in the values in this equation, 2 s i n 4 θ = 2 c o s 2 θ s i n 2 θ c o s 2 θ -2sin^{4}\theta=2cos^{2}\theta sin^{2}\theta-cos^{2}\theta

convert everything in terms of sine and obtain s i n θ = 1 3 sin\theta=\frac{1}{\sqrt{3}}

now by energy conservation the relation between v a n d v v and v^{'} is found to be v 2 = 2 g r + 3 g r v^{2}=2gr+\sqrt{3}gr

therefore a is 2 and b is 3.

But I know the general equation has tan theta as the coefficient of x so can you please explain

Sonali Das - 1 year, 4 months ago
Souvik Pal
Sep 26, 2016

It's an hc verma example question

Volume 1 page 130

Adhiraj Dutta - 1 year, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...